Let Hundred Flowers Bloom? The Rising of Local Authorities and the Governance of Agricultural Affairs in the French Countryside - Christine De Sainte Marie (European Regional Science Association (ERSA), 2010)
"Flowering Meadows" is the name of a new style of agri-environmental contract which has been included into the French Rural Development Plan 2007-2013. This contract is unusual in all respects. Management prescriptions are given up: the farmer is free to tend his meadow as he wants as long as he complies with an ecological performance. This performance is defined in a very simple way: a list of flower species among which 4, at least, must be found in each third of the meadow. This innovation has been proposed by the National Federation of Natural Regional Parks (NRP) which the farmers' organisations and the agricultural administration consider as a truly environmentalist institution they would like to keep only managing protected areas. However, NPRs have succeeded in implementing Flowering Meadows outside Natura 2000 sites. Since then, they claim to be considered as a fully fledge representative in reframing the agri-environmental policies. The paper will examine the rising of non agricultural actors in the gouvernance of agricultural affairs in the French countryside. To overcome the tension between global definition of conservation targets and objectives and the implementation of the Habitats directive, France has chosen to promote local agreements on biodiversity conservation, giving more power to local authorities among which the NRPs. I'll show how NRPs seized this opportunity to extend their conservation activities on farmlands by using the most powerful incentives of the modernization process: the Common Agricultural Policy's resources and the professional contest for excellence. Farmers could also find in Flowering Meadows contracts a legitimization of their activity and contribution to the society: producing food and producing biodiversity or ecosystem services (pollination). The scope and the limits of the rising of a territorial governance that could help farmers to switch from productionism to ecologically sound based agriculture will be discussed in the broader context.
Keywords: 330; environmental policy; agricultural activities; governance frameworks; political decentralisation; interplay; Natural regional parks